Habituasi Toleransi Beragama Santri Sebagai Jalan Dakwah Islam Rahmatan lil Alamin - Firdausi, Putri Nadiyatul (Institut Agama Islam Syarifuddin Lumajang, 2024)
Indonesia is a pluralistic country consisting of diverse religions, cultures and customs. Under the motto Bhineka Tunggal Ika, people coexist in a variety of religions, customs and cultures. Creating social integration and fostering an attitude of religious tolerance in a country with high religious diversity is not an easy thing. Especially in pondok pesantren with homogeneous santri conditions have their own challenges in efforts to foster the attitude of religious tolerance of their santri. Santri need to be given the cultivation of tolerance for other groups as an important part of preaching Islam as a religion of rahmatan lil alamin. This study aims to analyze the practice of habituation of religious tolerance of santri as a way of preaching Islam rahmatan lil alamin. This research is a descriptive qualitative research with purposive sampling technique. In this study, researchers conducted interviews with several pengasuh pondok pesantren and santri to analyze the practice of religious tolerance habituation. The results showed that the habituation of religious tolerance in pondok pesantren was carried out through 1) nationality workshops, 2) religious tolerance workshops, 3) charity activities, 4) activities with cross-religious communities, 5) sharing food on certain occasions, 6) santri service activities to the community, and 7) sharing berkat, and 8) education through various lessons in the curriculum that has been determined by each pesantren. Both pengasuh and santri of the pesantren expect the Kementerian Agama Republik Indonesia to initiate socialization and training activities on the concept of religious tolerance and share good practices of religious tolerance habituation with santri so that pengasuh and santri get a full understanding of religious moderation, especially religious tolerance.